ARphabet: Pembelajaran Abjad Inovatif Berbasis Augmented Reality untuk Anak Usia Dini - RM Chairil Andri; Revie Juniarti; Risna Oktaviati (LKP Unity Academy, 2025)
Letter recognition is a fundamental aspect of early childhood literacy development. Unfortunately, conventional media such as printed books and flashcards often lack appeal due to their limited ability to deliver simultaneous visual and auditory stimuli. This study aims to develop and evaluate an interactive Augmented Reality (AR)-based learning application called ARphabet, designed to assist young children in recognizing letters through 3D visualizations, supporting objects, and pronunciation audio. The application was developed using the Multimedia Development Life Cycle (MDLC), which includes the stages of concept, design, material collection, assembly, testing, and distribution. Evaluation was conducted through two approaches: expert validation using a questionnaire instrument with indicators including ease of use, effectiveness of content delivery, child appropriateness, and interactivity; and user testing using a quantitative approach through pre-tests and post-tests involving 21 kindergarten students. The expert validation results indicated a high feasibility score, with an average of 92.5%. Meanwhile, user testing showed that 90.5% of the children demonstrated improved letter recognition after using the application. These findings suggest that the use of AR technology can offer an innovative and effective solution to support early childhood literacy learning. The application also holds potential for further development, including syllable introduction, vocabulary building, or other age-appropriate educational content.